2016
DOI: 10.1371/journal.pone.0158395
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Growth Factor Receptor Mutation Enhances Expression of Cadherin-5 in Lung Cancer Cells

Abstract: Epidermal growth factor receptor (EGFR) activation has been shown to play a critical role in tumor angiogenesis. In this study, we investigate the correlation between EGFR mutations and cadherin-5 (CDH5), which is an angiogenic factor, in lung cancer cells. Increased expression CDH5 is observed in lung cancer cells with EGFR mutations. Stable lung cancer cell lines expressing mutant (exon 19 deletion E746-A750, and exon 21 missense mutation L858R) and wild type EGFR genes are established. A significantly highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 36 publications
1
25
0
Order By: Relevance
“…In this research, we demonstrated that EGFR enhanced glioma VM formation via increasing the expression levels of VE-cadherin, as well as the expression and activity levels of MMP-2 and MMP-9. Previous studies have shown that EGFR regulates VE-cadherin, MMP-2, and MMP-9 expression and function via the PI3K/AKT pathway, MEK/ERK pathway, and AKT pathway [58, 59]. The present study showed that EGFR increased VE-cadherin expression levels and MMP-2 and MMP-9 expression and activity levels via activating the PI3K/AKT pathway.…”
Section: Discussionsupporting
confidence: 70%
“…In this research, we demonstrated that EGFR enhanced glioma VM formation via increasing the expression levels of VE-cadherin, as well as the expression and activity levels of MMP-2 and MMP-9. Previous studies have shown that EGFR regulates VE-cadherin, MMP-2, and MMP-9 expression and function via the PI3K/AKT pathway, MEK/ERK pathway, and AKT pathway [58, 59]. The present study showed that EGFR increased VE-cadherin expression levels and MMP-2 and MMP-9 expression and activity levels via activating the PI3K/AKT pathway.…”
Section: Discussionsupporting
confidence: 70%
“…[ 21 ] Besides, another publication has shown an elevated expression of VE-cadherin in lung cancer cells related to increased angiogenesis and metastasis. [ 22 ] We also found that the cancer cells at the invasive front were positive for VE-cadherin [ Figure 4 ]. In addition, VE-cadherin positivity was found in the detached cells, especially around the vessels [ Figure 5 ].…”
Section: Discussionmentioning
confidence: 88%
“…Interestingly, missense mutations of the EGFR gene are only detected in distally recurrent glioblastoma cases, raising the possibility that EGFR mutation may be related to cellular migration and invasion. EGFR mutations have been reported to be involved in the stimulation of tumor angiogenesis, which is essential to metastasis (49,50). In particular, EGFR mutations have shown to significantly increase cellular migration and invasion via promoting angiogenesis in lung carcinoma cells (50).…”
Section: Discussionmentioning
confidence: 99%